ANALISIS PENDEKATAN TaRL DALAM PENINGKATAN KEMAMPUAN LITERASI MEMBACA SISWA KELAS III DI MIS TANGGA - Rahmi Ulfa; Syarifudin; Syarifuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the Teaching at the Right Level (TaRL) approach in improving reading literacy skills of third-grade students at MIS Tangga. The TaRL approach emphasizes instruction tailored to students' actual learning levels rather than their grade level. This descriptive qualitative research employed data collection techniques such as observation, interviews, documentation, and questionnaires. The results showed that most students responded very positively to the implementation of TaRL, with several questionnaire statements rated in the "very high" category (above 88%). Academically, students' final semester scores ranged from 80 to 91, with many showing stability or improvement, such as S1 (from 90 to 91) and S7 (from 85 to 87). These outcomes indicate that the TaRL approach effectively enhances student engagement, comprehension, and confidence in reading, while also positively influencing academic achievement. TaRL proves to be a viable and inclusive strategy for primary literacy education.